2004
DOI: 10.1029/2002jc001468
|View full text |Cite
|
Sign up to set email alerts
|

A large‐amplitude meander of the shelfbreak front during summer south of New England: Observations from the Shelfbreak PRIMER experiment

Abstract: [1] In order to examine spatial and temporal variability of the shelfbreak front during peak stratification, repeated surveys using a towed undulating vehicle (SeaSoar) are used to describe the evolution of shelfbreak frontal structure during 26 July to 1 August 1996 south of New England. Spatial correlation (e-folding) scales for the upper 60 m of the water column were generally between 8 and 15 km for temperature, salinity, and velocity. Temporal correlation scales were about 1 day. The frontal variability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 23 publications
(52 reference statements)
7
86
1
Order By: Relevance
“…At all five transects, the maximum alongshore flow is seen at the shelf break, with the highest speed of 0.25 m s −1 . This is the shelfbreak jet, documented by earlier studies (e.g., Chen and He, 2010;Gawarkiewicz et al, 2001Gawarkiewicz et al, , 2004Linder and Gawarkiewicz, 1998). Mean cross-shelf velocity maps (Fig.…”
Section: Mean Velocity and Thermohaline Structurementioning
confidence: 72%
See 2 more Smart Citations
“…At all five transects, the maximum alongshore flow is seen at the shelf break, with the highest speed of 0.25 m s −1 . This is the shelfbreak jet, documented by earlier studies (e.g., Chen and He, 2010;Gawarkiewicz et al, 2001Gawarkiewicz et al, , 2004Linder and Gawarkiewicz, 1998). Mean cross-shelf velocity maps (Fig.…”
Section: Mean Velocity and Thermohaline Structurementioning
confidence: 72%
“…In another study on a large WCR in 2006, we found that, over a timescale of 1 week, the WCR can significantly change the cross-shelf exchange of water mass, heat and salt (Chen et al, 2014). Other work also reported the significant role of eddy activities in the cross-shelf exchange (e.g., Gawarkiewicz et al, 2001Gawarkiewicz et al, , 2004Joyce et al, 1992). Measuring the cross-shelf transport at these locations will therefore be very challenging.…”
Section: Mean Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The general circulation on the New England Shelf is part of the larger shelf circulation of the Middle Atlantic Bight, which is characterized by a southwestward along-shelf flow of relatively fresh water, with across-shelf offshore currents at the surface and bottom and onshore currents in the middle of the water column [57]. Shelf water is separated from saltier slope water by a shelf-slope front, but exchanges between these water types can occur due to frontal instabilities [31], eddies [30], warm-core ring shelf interactions [22,48], and saline intrusions at the seasonal pycnocline [56]. Locally, there is a counter-clockwise recirculation just south of MVCO, which is strongest in the summer months [50].…”
Section: Synechococcus Diversity At Mvcomentioning
confidence: 99%
“…The undulations of the Scanfish were processed such that one up and one down cycle were averaged into a single vertical profile. Further details on the processing (for a SeaSoar vehicle) appear in Gawarkiewicz et al (2004). Horizontal spacing between profiles varied with water depth, but was typically between 0.5 and 2.0 km.…”
Section: Sampling Strategy and Methodsmentioning
confidence: 99%